PEMBELAJARAN DARING PARTOGRAF PADA MATA KULIAH ASUHAN KEBIDANAN PERSALINAN MASA PANDEMI - RETNANENGSIH,; RULY PRAPITASARI, (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
The COVID-19 pandemic has made so many changes in the teaching and learning process, especially in partographic learning done online. Partograf is a graph of the progress of childbirth to monitor the condition of the mother and fetus and detect the presence of abnormal childbirth and become a clue to early decision making. Partograph learning is one of the competencies that every student must have. The purpose of this study was to find out the differences in online partograph learning outcomes (knowledge and skills) in maternity care courses. This research was conducted using Quasi Experiment approach method with posttes research design with posttest only control group design. Sampling using total sampling techniques in the period July - August 2020 consists of 68 students. Data analysis using chi square test. The results showed that there were differences in the results of online learning manual and application-based partographs, knowledge p = 0.000 and skills p = 0.004. The conclusion of this study is that there are differences in the results of online learning (Knowledge and skills) partograph.